Vertical Tears of the Lateral Meniscus: Effects on In Vitro Tibiofemoral Joint Mechanics. Issue 8 (1st August 2014) - Goyal, Kanu S.; Pan, Tiffany J.; Tran, Diane; Dumpe, Samuel C.; Zhang, Xudong; Harner, Christopher D.
Background: Lateral meniscal tears are often seen with acute anterior cruciate ligament (ACL) injury and may be left in situ, repaired, or treated with meniscectomy. Clinical studies have shown good outcomes with vertical tears left in situ and poor outcomes following meniscectomy. However, clinically relevant studies are needed to establish a biomechanical foundation for treatment of these tears, particularly regarding the effects of meniscectomy. Purpose: To compare tibiofemoral joint mechanics following vertical lateral meniscal tears and meniscectomies. We hypothesized that a peripheral vertical tear of the lateral meniscus would alter joint mechanics, increasing contact pressure and area, and that more drastic effects would be seen following meniscectomy, at higher knee flexion angles, and with increased loads. Study Design: Controlled laboratory study. Methods: Ten fresh-frozen cadaveric knees (average age, 55 ± 12 years) were tested with 5 lateral meniscus states: intact, short vertical tear, extended vertical tear, posterior horn partial meniscectomy (rim intact), and posterior horn subtotal meniscectomy (rim excised). The specimens were loaded axially at knee flexion angles of 0°, 30°, and 60°, and musculotendinous forces were applied, simulating a 2-legged squat. Intra-articular contact pressures were measured using pressure-sensitive Fuji film. Kinematic data were acquired through digitization of fiducial markers. Results: Vertical tears did not cause a significant change in contact pressure or area. Partial meniscectomy increased maximum contact pressures in the lateral compartment at 30° and 60° from 5.3 MPa to 7.2 MPa and 7.6 MPa, respectively ( P = .02, P = .007). Subtotal meniscectomy (8.4 MPa) significantly increased contact pressure compared with partial meniscectomy (7.6 MPa) at 60° ( P = .04). Both meniscectomy states significantly increased contact pressures with increasing flexion from 0° to 60° ( P < .001, P < .001). Conclusion: Vertical tears of the lateral meniscus during a simulated 2-legged squat did not significantly change contact pressures and areas compared with an intact meniscus. However, treating these tears with partial and complete meniscectomy significantly increased maximum contact pressures. Clinical Relevance: Biomechanical evidence supports treating vertical lateral meniscus tears with meniscal-sparing techniques as opposed to meniscectomy, which may lead to progressive degenerative joint disease from altered joint biomechanics.